اتجاهات رواد المساجد نحو الخطاب المسجدي دراسة ميدانية بمساجد ولاية الوادي - زحاف, خديجة (University of Eloued جامعة الوادي, 2017)
هدفت هذه الدراسة إلى التعرف على اتجاهات رواد المساجد نحو الخطاب المسجدي، وتحددت الإشكالية بالصيغة التالية: ما هي اتجاهات رواد المساجد نحو الخطاب المسجدي؟ حيث اعتمدت على المنهج الوصفي بلغ حجم العينة(155) مفردة وزعت على رواد المساجد بمساجد ولاية الوادي بطريقة عشوائية معتمدة على أداة الاستبيان لجمع البيانات. وأبرز النتائج التي توصلت إليها الدراسة هي: • المسجد له دور فعال في توجيه وإرشاد ورفع مستوى الوعي لدى الناس. • أغلب أفراد عينة الدراسة يرون أن إمام مسجدهم يمثل قدوة بالنسبة لهم. • أغلب أفراد عينة الدراسة يرون أن الخطاب المسجدي لا يواكب متطلبات العصر The aim of this study is to identify the trends of the mosque's leaders towards the discourse of the mosque, and the problem is determined by the following formula: What are the trends of the mosque's leaders towards the discourse of the mosque? The descriptive approach was based on the descriptive approach. The sample size (155) was distributed to the mosque leaders in the mosques of the Wilayat of Al-Wadi in a random manner based on the questionnaire tool for data collection. The main findings of the study are: • The mosque has an effective role in directing, guiding and raising people's awareness. • Most members of the study sample believe that the Imam of their mosque is an example for them. • Most members of the study sample believe that the mosque discourse does not meet the requirements of the times
مذكرة ماستر تخصص دعوة واعلام
Keywords: الاتجاهات، رواد المساجد، الخطاب المسجدي; trends, mosque pioneers, mosque discourse.